Impact of Baby-Friendly Hospital Initiative for Improving Exclusive Breastfeeding: A Systemic Review of Ten Steps to Successful Breastfeeding - Fauziah, Nuraini; Riono, Pandu (KnE Life Sciences, 2021)
طThe Baby−Friendly Hospital Initiative (BFHI) launched by WHO / UNICEF has proven to be a powerful tool for raising breastfeeding rates. Breastfeeding is a protective factor for health, and breastfeeding promotion continues to be an important measure to improve child and maternal health in both developed and developing countries. A systematic review of the effect of BFHI worldwide found that the BFHI was the most effective intervention for improving breastfeeding rates at health system level and adherence to the Ten Steps positively affected short-, medium-, and long-term breastfeeding outcomes. This study therefore examines the impact of baby-friendly hospital initiatives for improving exclusive breastfeeding. This study used systematic review which performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The published literature was identified using relevant keywords. The initial screening was conducted by year of publication (8 years) and free full text, then reading the titles and abstracts. Nine articles were included in this review. The studies showed there were positive impacts in enhancement of exclusive breastfeeding after applied baby-friendly hospital initiative program. Rates of exclusive breastfeeding were demonstrably improved by applying BFHI with Ten Steps to Successful Breastfeeding at health care facilities to all mothers from pregnancy until postpartum. Keywords: Baby-Friendly Hospital Initiative, breastfeeding, exclusive breastfeeding, Ten Steps, Ten Steps to Successful Breastfeeding